Karakterisasi Simplisia Kunyit (Curcuma longa L) Menggunakan Hasil Pengeringan Sinar Matahari Dan Fluidized Bed Dryer - Arla Klisya Safitri; Supriyanto Supriyanto; Mojiono (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2026)
Fresh turmeric contains high moisture content that accelerates deterioration and reduces quality and shelf life; therefore, an effective drying method is required to preserve the quality of turmeric simplicia. This study aimed to compare the characteristics of turmeric simplicia dried using sun drying and a Fluidized Bed Dryer (FBD). The experiment was arranged in a Completely Randomized Design (CRD) with two drying treatments and three replications. FBD drying was conducted at 50°C with an airflow velocity of 2 m/s until the final moisture content reached <10% (wet basis), while sun drying was performed until the same moisture target was achieved. The observed parameters included weight loss, drying rate, shrinkage area, color, and curcumin content. Data were analyzed using analysis of variance (ANOVA) at a 95% confidence level (α = 0.05), followed by a post hoc test when significant differences were detected. The results showed that FBD drying produced a faster drying rate, better maintained material shape and size with lower shrinkage, resulted in brighter color, and preserved higher curcumin content (11.23 mg/g) compared to sun drying (9.67 mg/g). These findings indicate that the FBD method is more efficient and capable of producing higher-quality turmeric simplicia for herbal and pharmaceutical applications.